An Amplitude Modulation/Demodulation Scheme for Whisker-Based Texture Perception - Boubenec, Yves (J Neurosci, 2014)
Whisking rodents can discriminate finely textured objects using their vibrissae. The biomechanical and neural processes underlying such sensory tasks remain elusive. Here we combine the use of model micropatterned substrates and high-resolution videography of rats' whiskers during tactile exploration to study how texture information is mechanically encoded in the whisker motion. A biomechanical modeling of the whisker is developed, which yields quantitative predictions of the spectral and temporal characteristics of the observed whisker kinetics, for any given topography. These texture-induced whisker vibrations are then replayed via a multiwhisker stimulator while recording neuronal responses in the barrel field of the primary somatosensory cortex (S1bf). These results provide a comprehensive description of the transduction process at play during fine texture sensing in rats. They suggest that the sensory system operates through a vibratory amplitude modulation/demodulation scheme. Fine textural properties are encoded in the time-varying envelope of the whisker-resonant vibrations. This quantity is then recovered by neural demodulation, as it effectively drives the spiking-rate signal of a large fraction of S1 cortical neurons. This encoding/decoding scheme is shown to be robust against variations in exploratory conditions, such as the scanning speed or pad-to-substrate distance, thus allowing for reliable tactile discrimination in realistic conditions.